Femmes et films de guerre en Grande-Bretagne (1939-1945) : signes d’émancipation ou cas de manipulation ? - Elizabeth de Cacqueray (Revue LISA)
This article analyzes the representation of women in a certain number of filmic texts released in Great Britain between 1939 and 1945: more particularly, Fires Were Started, Millions Like Us and Went the Day Well? The innovatory roles these films offer to women have led me to ask whether the representation corresponds to a reflection of a genuine situation at the time or whether it is the result of a manipulation of the image of women in the interests of propaganda. The filmic representations are compared to a well-known Women’s Auxiliary Air Force recruitment poster, an example of direct propaganda, and to women’s personal accounts of their war-time experiences. Similarities in method between the poster and the films emerge which underline the propaganda slant of the films. Certain aspects of the women’s accounts confirm the representation of women provided by the films, thus supporting the theory whereby the films reflect the relatively emancipating effects of the war for women. However, the examination of these accounts also reveals the extent to which the films omit certain aspects of women’s war experiences: the sometimes negative attitudes of men towards women in the work place, the trauma for mothers around the evacuation of their children […] The propaganda slant of the films is thus as much due to what they omit to mention as it is due to the image of women which reaches the screen.